SUICIDE IN MILITARY PERSONNEL. ITS SOCIOPSYCHOLOGICAL CAUSES (World Bulletin of Management and Law, 2024)
In this article, socio-psychological problems in military communities and problems inherent in the Armed Forces of the Republic of Uzbekistan are part of the problems of the general community. Because, since the armed forces are part of society, it is impossible to exist separately, out of these problems
Keywords: Socio-psychological; problems; suicidal